2007
DOI: 10.1016/j.brainres.2006.06.091
|View full text |Cite
|
Sign up to set email alerts
|

Establishing reference in language comprehension: An electrophysiological perspective

Abstract: The electrophysiology of language comprehension has long been dominated by research on syntactic and semantic integration. However, to understand expressions like "he did it" or "the little girl", combining word meanings in accordance with semantic and syntactic constraints is not enough-readers and listeners also need to work out what or who is being referred to. We review our event-related brain potential research on the processes involved in establishing reference, and present a new experiment in which we e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
217
5

Year Published

2007
2007
2015
2015

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 194 publications
(252 citation statements)
references
References 53 publications
30
217
5
Order By: Relevance
“…In line with earlier ERP research (e.g., Nieuwland and Van Berkum, 2006a;Van Berkum et al, 2007), the present findings thus show that the language comprehension system relies on different neural mechanisms to deal with referential ambiguity, referential failure and semantic anomaly. Moreover, a closer examination of relative activation increases and decreases across different brain regions for all conditions revealed an intriguing pattern of results.…”
Section: Referential Ambiguity and Medial Prefrontal Regionssupporting
confidence: 92%
See 2 more Smart Citations
“…In line with earlier ERP research (e.g., Nieuwland and Van Berkum, 2006a;Van Berkum et al, 2007), the present findings thus show that the language comprehension system relies on different neural mechanisms to deal with referential ambiguity, referential failure and semantic anomaly. Moreover, a closer examination of relative activation increases and decreases across different brain regions for all conditions revealed an intriguing pattern of results.…”
Section: Referential Ambiguity and Medial Prefrontal Regionssupporting
confidence: 92%
“…Referential failure and sentence-external anaphoric inferences Also consistent with our predictions, referentially failing pronouns elicited increased BOLD responses in medial and bilateral parietal, and left middle frontal brain regions (e.g., Hammer et al, 2007;Kuperberg et al, 2003;Newman et al, 2001;Ni et al, 2000), supporting the notion that readers initially ascribed referential failure to a problem with the morpho-syntactic gender of the pronoun (e.g., Osterhout and Mobley, 1995;Van Berkum et al, 2007).…”
Section: Referential Ambiguity and Medial Prefrontal Regionssupporting
confidence: 85%
See 1 more Smart Citation
“…Given that the gender of the determiner (-o/-a) was grammatically correct or incorrect given that of the antecedent (camiseta), grammatically incorrect determiners in our study may thus initially be perceived as a morphosyntactic "dead end", triggering re-analysis (Gouvea et al, 2010;Kaan and Swaab, 2003;Osterhout and Holcomb, 1992). Perhaps for similar reasons, pronouns with unexpected or incorrect gender-marking will also evoke P600 effects (e.g., Nieuwland and Van Berkum, 2006;Osterhout and Mobley, 1995;Van Berkum et al, 2007;Xiang et al, 2009).…”
Section: Predictions For Event-related Brain Potentialsmentioning
confidence: 77%
“…Critically, under any neurocognitive account of sentence comprehension (Bornkessel-Schlesewsky and Schlesewsky, 2009a;Friederici, 2002;Hagoort, 2005), this outright syntactic violation should have evoked a P600 effect, which is the ERP effect most commonly associated with syntactically problematic or dispreferred linguistic expressions Van Berkum et al, 2007;Kutas et al, 2006). Moreover, a multitude of electrophysiological studies have reported P600 effects for related gender mismatch violations across different languages (Barber and Carreiras, 2005;Molinaro et al, 2011;Wicha et al, 2004;Van Berkum et al, 2007;Xiang et al, 2009). The fact that the main manipulation in the current study elicited a sustained negativity rather than a P600 effect suggests that the processing consequences of incorrectly gender-marked ellipsis can be qualitatively different from the repair or reanalysis processes as assumed to be indexed by P600 modulations, and perhaps that participants did not treat failure to retrieve an antecedent as a consequence of the gender agreement violation.…”
Section: Discussionmentioning
confidence: 99%